2017
DOI: 10.1038/srep43154
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti-inflammatory drugs modulate cellular glycosaminoglycan synthesis by affecting EGFR and PI3K signaling pathways

Abstract: In this report, selected non-steroidal anti-inflammatory drugs (NSAIDs), indomethacin and nimesulide, and analgesics acetaminophen, alone, as well as in combination with isoflavone genistein as potential glycosaminoglycan (GAG) metabolism modulators were considered for the treatment of mucopolysaccharidoses (MPSs) with neurological symptoms due to the effective blood-brain barrier (BBB) penetration properties of these compounds. We found that indomethacin and nimesulide, but not acetaminophen, inhibited GAG sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previous work has reported the importance of the PI3K pathway as an important regulator of growth and inflammation in inflammation-mediated diseases such as psoriasis [ 58 ]. Moreover, studies indicated that genistein, alone or even in combination with various pharmaceutical agents (e.g., selected non-steroidal anti-inflammatory drugs), inhibits EGF receptor kinase and its downstream effector PI3K, which in turn might also be implicated in NF-κB transcriptional activation [ 59 , 60 ]. Thus, to test these correlations, we primarily examined the activity of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported the importance of the PI3K pathway as an important regulator of growth and inflammation in inflammation-mediated diseases such as psoriasis [ 58 ]. Moreover, studies indicated that genistein, alone or even in combination with various pharmaceutical agents (e.g., selected non-steroidal anti-inflammatory drugs), inhibits EGF receptor kinase and its downstream effector PI3K, which in turn might also be implicated in NF-κB transcriptional activation [ 59 , 60 ]. Thus, to test these correlations, we primarily examined the activity of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the neuroprotective effects of GE mainly involved several mechanisms such as resisting the oxidative stress damage, alleviating neuroinflammation, reducing Aβ deposition, activating the neurotrophins and antiapoptotic factors ( Yang et al, 2014 ). Besides, as a lipid-soluble flavonoid compound, GE has the effective BBB penetration properties ( Mozolewski et al, 2017 ). All these studies together suggest that GE may be a potential agent for the treatment of the neurodegenerative disease and it is noteworthy to further explore the neuroprotective effects of GE.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that anti-inflammatory agents, such as non-steroidal anti-inflammatory drugs (NSAIDs), have a beneficial effect on AD, and several reports have shown that NSAIDs protect against inflammation in transgenic AD models [56]. It has been shown that some NSAIDs can exert their actions by modulating PI3K [75,76,77]. Thus, an interesting line of investigation is now directed at analyzing the relationship between inflammation, PI3K signaling, and AD.…”
Section: The Role Of Pi3k In Neuroinflammationmentioning
confidence: 99%